2016
DOI: 10.1155/2016/3707406
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin A Derivative All-Trans Retinoic Acid Repairs Amyloid-β-Induced Double-Strand Breaks in Neural Cells and in the Murine Neocortex

Abstract: The amyloid-β peptide or Aβ is the key player in the amyloid-cascade hypothesis of Alzheimer's disease. Aβ appears to trigger cell death but also production of double-strand breaks (DSBs) in aging and Alzheimer's disease. All-trans retinoic acid (RA), a derivative of vitamin A, was already known for its neuroprotective effects against the amyloid cascade. It diminishes, for instance, the production of Aβ peptides and their oligomerisation. In the present work we investigated the possible implication of RA rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
2
13
1
Order By: Relevance
“…This clearly illustrates the effect of Aβ on DSB production and of the counteracting effect of RA, i.e., an effect that can either be reparative (RA added after Aβ) or protective (RA added at the same time or before Aβ). Whereas in a previous publication we demonstrated that RA can repair Aβ-induced DSBs [27], in the present work, we showed that RA also prevents Aβ-induced DSBs. RA can do it not only in SH-SY5Y and astrocytic DI TNC 1 cells but also in the neocortex of young and aged C57BL/6J mice.…”
contrasting
confidence: 74%
See 4 more Smart Citations
“…This clearly illustrates the effect of Aβ on DSB production and of the counteracting effect of RA, i.e., an effect that can either be reparative (RA added after Aβ) or protective (RA added at the same time or before Aβ). Whereas in a previous publication we demonstrated that RA can repair Aβ-induced DSBs [27], in the present work, we showed that RA also prevents Aβ-induced DSBs. RA can do it not only in SH-SY5Y and astrocytic DI TNC 1 cells but also in the neocortex of young and aged C57BL/6J mice.…”
contrasting
confidence: 74%
“…Thus, by changing the expression of enzymes of the amyloid cascade, RA might also prevent the formation of Aβ-induced DSBs and be a factor of neuroprotection against Aβ-induced DSBs and not just of DSB repair. The aim of the present study was to demonstrate that indeed RA not only repairs Aβ-induced DSBs, as described in our previous publication [27], but also prevents their occurrence. For such a purpose, neuroprotective experiments have been carried out with RA added before or at the same time as Aβ and not after as in repair experiments.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations